Penerapan Model Kooperatif Tipe Jigsaw pada Mata Pelajaran Matematika Kelas V SD Hasanuddin - Jelyta Silaen; Esra Arta Uli Gultom; Kris Jernih Puspita Ziliwu; Kasih Pirman Waruwu; Taruli Marito Silalahi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to determine the application of the jigsaw type cooperative learning model to fifth grade students at Hasanuddin Elementary School, Medan Helvetia, in the mathematics subject of integers. This type of research uses PTK (Classroom Action Research). The subjects in this research were all 30 fifth grade students at Hasanuddin Elementary School, consisting of 13 men and 17 women. Meanwhile, the object of this researcher is to improve student learning outcomes in mathematics subjects covering integers. We can observe data on the comprehension abilities of class V students in classes using the Jigsaw model in table 1, then the data is analyzed using the SPSS version 25.0 application. The results of data analysis show that the learning outcomes in class V using the Jigsaw model obtained a class average score of 83.30. The average value of students' mathematical understanding was classified as good, followed by the highest score obtained by class V students at Hasanudin Elementary School was 100. 00 and the lowest value is 63.00. Based on data processing on the mathematical understanding ability of fifth grade students at Hasanuddin Elementary School using the Jigsaw model, it is known that 3 students got scores in the range of 56-70 (medium category) or 10.0% of the entire sample, 14 students got scores in the range. 71-85 (good category) or 46.7% of the entire sample, and 13 students got scores in the range of 86-100 (very good category) or 43.3% of the entire sample.